A study on the genus Anaches Pascoe, 1865 (Coleoptera, Cerambycidae, Lamiinae, Pteropliini), with a new species and two new synonyms - Lin, Mei-Ying; Weigel, Andreas (Zootaxa, 2022)
A new species, Anaches m-signatus sp. nov. is described from Zhejiang, Hunan and Guangxi Provinces, China. Sthenias semicylindricus Hayashi, 1974 and Sthenias murzini Lazarev, 2020 are synonymized with Anaches medioalbus (Breuning, 1956). Three similar species are compared with additional pictures and descriptions.